2015
DOI: 10.1158/1541-7786.mcr-14-0142
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Slit2 Activity Impairs VEGF-Induced Angiogenesis and Tumor Neovascularization in EphA2-Deficient Endothelium

Abstract: Angiogenic remodeling during embryonic development and in adult tissue homeostasis is orchestrated by cooperative signaling between several distinct molecular pathways, which are often exploited by tumors. Indeed, tumors upregulate pro-angiogenic molecules while simultaneously suppressing angiostatic pathways in order to recruit blood vessels for growth, survival, and metastatic spread. Understanding how cancers exploit pro- and anti-angiogenic signals is a key step in developing new, molecularly targeted anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The present study provided evidence to suggest that Slit2 may inhibit vascular endothelial cell migration in vitro in a dose-dependent manner, which is consistent with the findings of previous studies (12,3335,37). Youngblood et al reported that inhibiting Slit activity rescued VEGF-induced angiogenesis in vitro and in vivo , as well as VEGF-dependent tumor angiogenesis in EPH receptor A2 (EphA2)-deficient endothelial cells and animals (38). Furthermore, suppressing Slit activity or Slit2 expression in EphA2-deficient endothelial cells has been revealed to restore VEGF-induced activation of Src and Rac, which are required for VEGF-mediated angiogenesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…The present study provided evidence to suggest that Slit2 may inhibit vascular endothelial cell migration in vitro in a dose-dependent manner, which is consistent with the findings of previous studies (12,3335,37). Youngblood et al reported that inhibiting Slit activity rescued VEGF-induced angiogenesis in vitro and in vivo , as well as VEGF-dependent tumor angiogenesis in EPH receptor A2 (EphA2)-deficient endothelial cells and animals (38). Furthermore, suppressing Slit activity or Slit2 expression in EphA2-deficient endothelial cells has been revealed to restore VEGF-induced activation of Src and Rac, which are required for VEGF-mediated angiogenesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…The sponge angiogenesis assay was performed as described previously [ 26 , 27 ]. Briefly, gel foam sponges (Pharmacia & Upjohn Co, New York, NY) were cut into pieces (2.5–3 mm wide by 5 mm long) and soaked with 100 μl of PBS containing 100 ng of human VEGF (R&D Systems Inc.) plus 100 pmol of a CD148-interacting trimeric TSP1 fragment or vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…EphA2 belongs to the EphA subclass, and is expressed at a minimal level in epithelial cells (33). There is evidence that high levels of EphA2 promote various aspects of the malignant phenotype, including cell growth, angiogenesis, migration, invasion and survival of cancer cells (34,35). A previous study reported that there is a correlation between EphA2 and high levels of angiogenesis markers, in particular, VEGF expression and MVD counts, in HCC tumorigenesis (36,37).…”
Section: Discussionmentioning
confidence: 99%